MODY calculator applied in patients with clinical diagnosis of type 1 diabetes mellitus: Is a higher cutoff needed? - Peghinelli, Vinícius Vigliazzi [UNESP]; De Sibio, Maria Teresa [UNESP]; Depra, Igor de Carvalho [UNESP]; Teles Bezerra, Milena Gurgel; Sakalem, Marna Eliana; Júnior, Adriano Francisco De Marchi [UNESP]; da Rocha, Paula Barreto [UNESP]; Tilli, Helena Paim [UNESP]; Gonçalves, Bianca Mariani [UNESP]; Vieira, Ester Mariane [UNESP]; Lourenço, Mariana Menezes [UNESP]; Nogueira, Célia Regina [UNESP] (Elsevier, 2024)
Aim: This study aimed to evaluate the mean post-test probability (PTP) of the Maturity-onset diabetes of the young (MODY) calculator in a multiethnic cohort of patients previously diagnosed with type 1 diabetes (T1DM). Materials and methods: The MODY probability calculator proposed by Shields and colleagues (2012) was applied to 117 patients from a T1DM outpatient clinic at a tertiary hospital in Brazil. Additionally, two exons of the HNF1A gene were sequenced in eight patients who hadn't received insulin treatment within six months after the diagnosis. Results: 17.1 % of patients achieved PTP >10 %; 11.1 % achieved PTP >25 % (and all patients >30 %), and 7.7 % achieved PTP >40 %. Among the patients who were selected for genetic sequencing, 100 % presented PTP >30 %, with 66.6 % achieving PTP >40 % and 41.6 % achieving PTP >75 %. These cutoffs are as suggested for the Brazilian population, according to previous investigations. No mutation was observed in the sequenced exons. Conclusion: Considering that only around 10 % of the evaluated cases achieved PTP >30 %, it is highly probable that the most suitable cutoff to select patients for genetic sequencing in a Brazilian cohort of T1DM is higher than the cutoff used in Caucasian populations.
Keywords: Clinic prediction model; Genetic sequencing; MODY; Monogenic diabetes